Preparation of Thin Films from New Azolic Copolymers and Investigation of Their Membrane Properties - Sinirlioglu, Deniz; Muftuoglu, Ali Ekrem; Bozkurt, Ayhan (TAYLOR & FRANCIS INC, 2014)
The preparation and thermal, morphological, electrochemical and proton conducting properties analysis of new azolic copolymers based on 2-acrylamido-2-methyl-1-propanesulfonic acid (AMPS) and 5-(methacrylamido)tetrazole) (MTet) were performed throughout this work. MTet monomer, prepared by the reaction of methacryloyl chloride with 5-aminotetrazole, was copolymerized with AMPS via conventional free radical copolymerization at different monomer feed ratios to achieve poly(MTet-co-AMPS) copolymer membranes. The obtained copolymer membranes were analyzed by FTIR, H-1-NMR, thermogravimetric analysis (TGA), differantial scanning calorimetry (DSC), Elemental Analysis (EA), Cyclic Voltammetry (CV), and Impedance Spectroscopy. The composition of copolymers was determined via elemental analysis (EA). TGA demonstrated that the copolymer electrolyte membranes are thermally stable up to approximately 250 degrees C. The appearance of a single T-g in the DSC curves verified the homogeneity of the membranes. CV curves demonstrated the oxidative stability of the samples in 3V region. The methanol permeabilities of S1, S2 and S3 copolymers were determined as 1.60x10(-9) mol cm(-2) s(-1), 2.71x10(-9) mol cm(-2) s(-1) and 3.32x10(-9) mol cm(-2) s(-1), respectively, which were comparable with that of Nafion 112 (1.89x10(-9) mol cm(-2) s(-1)). In the anhydrous conditions, the maximum proton conductivity was determined as 0.009 Scm(-1) at 150 degrees C for poly(MTet-co-AMPS) (S3). The proton conductivity and methanol permeability of poly(MTet-co-AMPS) copolymer membranes increased gradually with the increase of AMPS content. These results suggested that the poly(MTet-co-AMPS) copolymer membranes were particularly promising to be used as proton exchange membranes in PEMFCs.
Keywords: proton conductivity; copolymer; polymer electrolyte; fuel cell; 5-(methacrylamido)tetrazole; 2-acrylamido-2-methyl-1-propanesulfonic acid; PROTON-CONDUCTING PROPERTIES; ACID; NAFION; Polymer Science